Answer:50.27 centimeters
Step-by-step explanation:
ANSWER
EXPLANATION
The given inequality is,
By the definition of absolute value,
We divide through by negative 1, in the first part of the inequality and reverse the sign to get,
We simplify now to get,
Divide through by 2 to obtain,
Step-by-step explanation:
s is inversely proportional to t
If s= 0.6 , t= 4
s=k/t
0.6= k/4
k=2.4
If s=12, then
t=k/s
t=2.4/12
t=0.05
Hey there!!
Given equation :
... -4 ( x + 10 ) - 6 = -3 ( x - 2 )
Using the distributive property :
... -4x - 40 - 6 = -3x + 6
Combining like terms :
... -4x - 46 = -3x + 6
Adding 46 on both sides :
... -4x = -3x + 52
Adding 3x on both sides :
... -x = 52
... x = -52
Hope helps!
Answer:
d (f-g)(x)=(5]-6 this is a brainly answer